Preprocedural Imaging - Jing, Mingxue; Yeo, Joshua Y.P; Holmin, Staffan; Andersson, Tommy; Arnberg, Fabian; Bhogal, Paul; Yang, Cunli (Clinical neuroradiology (Munich), 2022)
Background Endovascular treatment (EVT) has strong evidence for its effectiveness in treatment of acute ischemic stroke (AIS); however, up to half of the patients who undergo EVT still do not have good functional outcomes. Various prethrombectomy radiological factors have been shown to be associated with good clinical outcomes and may be the key to better functional outcomes, reduced complications, and reduced mortality. In this paper, we reviewed the current literature on these imaging parameters so they can be employed to better estimate the probability of procedural success, therefore allowing for more effective preprocedural planning of EVT strategies. We reviewed articles in the literature related to imaging factors which have been shown to be associated with EVT success. The factors which are reviewed in this paper included: anatomical factors such as 1) the type of aortic arch and its characteristics, 2) the characteristics of the thrombus such as length, clot burden, permeability, location, 3) the middle cerebral artery features including the tortuosity and underlying intracranial stenosis, 4) perfusion scans estimating the volume of infarct and the penumbra and 5) the effect of collaterals on the procedure. The prognostic effect of each factor on the successful outcome of EVT is described. The identification of preprocedural thrombectomy imaging factors can help to improve the chances of recanalization, functional outcomes, and mortality. It allows the interventionist to make time-sensitive decisions in the treatment of acute ischemic stroke.